Reactivation of Pulmonary Tuberculosis following Treatment of Myelofibrosis with Ruxolitinib - Maheen Z. Abidi; Javeria Haque; Parvathi Varma; Horatiu Olteanu; Guru Subramanian Guru Murthy; Binod Dhakal; Parameswaran Hari (Case Reports in Hematology)
Ruxolitinib is widely in use for treatment of myeloproliferative disorders. It causes inhibition of the Janus kinase (JAK) signal transducer and activation of transcription (STAT) pathway, which plays a key role in the underlying pathophysiology of myeloproliferative diseases. We describe a case of reactivation pulmonary tuberculosis in a retired physician while on treatment with ruxolitinib. We also review the literature on opportunistic infections following use of ruxolitinib. Our case highlights the importance of screening for latent tuberculosis in patients from highly endemic areas prior to start of therapy with ruxolitinib.